Victorian politics and politics overseas - Middleton, A (Cambridge University Press, 2020)
This review explores recent historiography on the international and imperial dimensions of nineteenth-century British politics. In particular, it charts historians' attempts to assess how British engagement with politics overseas - in Europe, the empire, and the 'rest of the world' - helped to shape domestic political structures, cultures, and ideologies. While concentrating mainly on studies produced during the last twenty years, the review also affirms the continued relevance of work from before the turn of the century, and suggests that some of the most compelling approaches to connecting 'domestic' and 'international' politics may lie in older historiography. It proposes also that political historians might engage more closely with relevant scholarship by intellectual historians and historians of political thought.